Minimum wages, fringe benefits, and working conditions - Wessels, Walter J. (Washington, D. C. : American Enterprise Institute for Public Policy Research, 1980)
This monograph presents a model of minimum wages that incorporates the assumption that employers react to minimum-wage increases by trying to offset their higher wage costs.
Includes bibliographical references.
aia 21/03/2019
Loans
Keywords: Minimum wage -- Mathematical models; Non-wage payments-- Mathematical models; Employee fringe benefits -- Mathematical models; Hours of labour -- Mathematical models; Labour supply -- Mathematical models